Crosslink‐Enhanced Emission Effect on Luminescence in Polymers: Advances and Perspectives. (1st April 2020) - Tao, Songyuan; Zhu, Shoujun; Feng, Tanglue; Zheng, Chengyu; Yang, Bai
Abstract: The crosslink‐enhanced emission effect was first proposed to explore the strong luminescence of nonconjugated polymer dots possessing only either non‐emissive or weakly emissive sub‐luminophores. Interesting phenomena in recent research indicate such enhancement caused by extensive crosslinking appears in diverse luminescent polymers with sub‐luminophores (electron‐rich heteroatomic moieties) or luminophores (conjugated π domains). This enhancement can promote the emission from nonluminous to luminous, from weakly luminous to strongly luminous, and even convert the pathway of radiative transitions. The concept of the crosslink‐enhanced emission effect should be updated and extended to an in‐depth spatial effect, such as electron overlap and energy splitting in confined domains by effective crosslinking, more than initial immobilization. This Minireview outlines the development of the crosslink‐enhanced emission effect from the perspective of the detailed classification, inherent mechanism and applicable systems. An outlook on the further exploration and application of this theory are also proposed. Abstract : Strong links : Polymers containing luminophores or sub‐luminophores may display enhanced emission upon crosslinking by covalent, supramolecular, and ionic bonding, and by through‐space interactions in confined domains. In this Minireview the theoretical background is discussed and numerous examples are provided, which may guide researchers in crosslinkage techniques to improve luminescent systems.